2006
DOI: 10.1590/s0004-27302006000400027
|View full text |Cite
|
Sign up to set email alerts
|

Renal stone disease: causes, evaluation and medical treatment

Abstract: The purpose of the present review is to provide an update about the most common risk factors or medical conditions associated with renal stone formation, the current methods available for metabolic investigation, dietary recommendations and medical treatment. Laboratory investigation of hypercalciuria, hyperuricosuria, hyperoxaluria, cystinuria, hypocitraturia, renal tubular acidosis, urinary tract infection and reduction of urinary volume is based on the results of 24-hr urine collection and a spot urine for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 58 publications
0
53
0
8
Order By: Relevance
“…8 In recent studies, remarkable improvement has been observed in the majority of these clinical conditions with the treatment of IHC. [8][9][10][11][12][13][14][15][16] Since many of these conditions including UTI may also lead to significant morbidity and mortality in children, identification of IHC is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…8 In recent studies, remarkable improvement has been observed in the majority of these clinical conditions with the treatment of IHC. [8][9][10][11][12][13][14][15][16] Since many of these conditions including UTI may also lead to significant morbidity and mortality in children, identification of IHC is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…The study of these layers, as conducted in the present morphological analysis, provides a better understanding of the genesis of individual stones. Knowledge of the origin of the stone and the factors involved in the lithogenic process is helpful when prescribing a diet or therapy intended to reduce the risk of recurrence 10,11 . Without treatment, the risk of recurrence of CaOx stones is 10% in one year, 33% in 5 years and 50% in 10 years 12 .…”
Section: Discussionmentioning
confidence: 99%
“…La sobresaturación urinaria de diferentes metabolitos como el calcio, oxalato y úrico influye de manera positiva en la litogénesis, mientras que el aumento en orina de citrato y magnesio disminuye el riesgo de formación de litiasis al actual como inhibidores de la precipitación cristalina (11,12,13). Aunque la composición de la litiasis tiene en cierta manera que ver y se relaciona con las alteraciones metabólicas urinarias (7,14), es cierto que el análisis de los factores en sangre y orina es básico a la hora de establecer medidas profilácticas y preventivas.…”
Section: Discussionunclassified